2022
DOI: 10.1007/s40519-022-01448-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the Female Muscularity Scale among Chinese young women

Abstract: Purpose: The Female Muscularity Scale (FMS) was speci cally developed for assessing drive for muscularity in women. The current study aimed to translate the FMS into Chinese (FMS-C) and examine its psychometric properties among Chinese young women.Methods: Based on standard procedures, the FMS was translated into Chinese. With a sample of 517 Chinese women college students ( = 18.86 years), the current study examined the factor structure, reliability, and convergent and incremental validity of the FMS-C.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Such a finding was expected as previous research has shown that muscularity is not the sociocultural feminine standard of attractiveness in the Chinese culture ( 40 ). Moreover, there is evidence in the literature suggesting that Chinese females have a lower motivation to exercise and a lower level of internalization for muscularity comparison to females in western societies ( 41 , 42 ). The sociocultural ideal of female beauty that is commonly mentioned in the Chinese culture includes attributes such as being tall and curvy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a finding was expected as previous research has shown that muscularity is not the sociocultural feminine standard of attractiveness in the Chinese culture ( 40 ). Moreover, there is evidence in the literature suggesting that Chinese females have a lower motivation to exercise and a lower level of internalization for muscularity comparison to females in western societies ( 41 , 42 ). The sociocultural ideal of female beauty that is commonly mentioned in the Chinese culture includes attributes such as being tall and curvy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence in the literature Confirmatory factor analysis for female adolescents. suggesting that Chinese females have a lower motivation to exercise and a lower level of internalization for muscularity comparison to females in western societies (41,42). The sociocultural ideal of female beauty that is commonly mentioned in the Chinese culture includes attributes such as being tall and curvy (40).…”
Section: Internal Consistencymentioning
confidence: 99%
“…Higher total scores of the FMS indicated higher levels of drive for muscularity in women. The FMS has been validated in the Chinese context and presented good internal consistency reliability ( α = .91), test–retest reliability, and construct validity in Chinese adult women (Tang et al, 2022). In the current study, the FMS had a Cronbach's α of .90 and a McDonald's ω of .91.…”
Section: Methodsmentioning
confidence: 99%
“…In China, as reflected by the rapidly increasing number of bodybuilding-related videos for women in Chinese popular social media platforms (e.g., Bilibili, Xiaohongshu, and TikTok/Douyin), bodybuilding and fitness training are becoming new trends for Chinese women (Tang et al, 2022). As discussed in Gong (2023), exposure to this type of social media content may exacerbate Chinese women's appearance anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Negative muscle talk, generally researched in men, has been found to be closely linked to men's thinness-oriented body dissatisfaction and thinness-oriented disordered eating [14,15], as well as men's muscularity-oriented body dissatisfaction (e.g., muscularity dissatisfaction and muscle dysmorphia) and expectations of steroid use [8,14]. Notably, although social and media pressures for being muscular have been increasing for women and more research is needed for muscularity concerns in women [16,17], research evidence on muscle talk in women is still very limited. However, with a sample of women from the U.S., one recent study showed that muscle talk was closely related to higher muscularity dissatisfaction in women [7].…”
Section: Body Talk Body Image and Disordered Eatingmentioning
confidence: 99%